Development of Interactive Virtual Reality Application for Simulating Experimental Tensile Test - Rivai Wardhani; Naufal Alfandra Setyawan ; Moh. Rafi Bima Adi Saputra (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Information technology has significantly transformed traditional educational systems into adaptable forms of learning. Experimental tension test is a practical study included in the mechanical engineering curriculum, specifically as a part of Material and Metallurgy. The fundamental issue arises from the deficiency in comprehending the understanding of mechanical properties, which is a result of traditional educational methods. Virtual reality (VR) technology enhances the comprehension of the study of material properties for students studying mechanical engineering. This study presents a virtual reality tool, called VR experimental tensile test. It is intended to be utilized in flexible learning. Students as a user can investigate and examine the utilization of the program for learning and conducting safety lab orientation. The application evaluation was conducted using the User Experience Questionnaire (UEQ). This study suggests that using 3D model visualization in the virtual reality application enhances user experiences in learning tensile test and follow its lab orientation.